Textbook of oral and maxillofacial surgery - Malik, Neelima Anil (New Delhi : Jaypee Brothers Medical Publishers (P) Ltd., 2012)
Extensive, point wise coverage of the subject of maxillofacial surgery following the syllabus of all the universities in India and Asia. Well illustrated with many line drawings, flow charts, clinical photograph's, radiographs, CT scans, MRI and scintigraphic pictures. Provides the latest updates and internationally accepted classifications of various oral and maxillofacial disorders. All clinical materials from the reputed teaching institutes. And much more!! DVD 1 contains: Aseptic preparation of the patient along with surgical draping for Oral and Maxillofacial surgeries. Surgical demonstration for removal of impacted supernumerary tooth in maxillary right anterior region and lower left mandibular premolar teeth region with two impacted supernumerary teeth. Surgical demonstration of Labial Maxillary Frenectomy procedure. DVD 2 contain: Surgical extraction of lower right impacted third molar in the edentulous area. Surgical demonstration for exposure of supper right canine (for fixing the orthodontic bonding) and extraction of the right deciduous canine. Surgical procedure for the cyst enucleation in anterior region of the maxilla. Patient had recurrent swelling, pus discharge and periodontally compromised anterior teeth. 3D-CT scan helpful in planning the surgical treatment. Presenting a 3D-CT scan of the entire skull of a patient, who was involved in road traffic accident. The fracture of the life parasymphysis and right subcondylar region is seen in all the rotations / in all the planes, which is not possible to visualize by routine X-ray pictures. Shows 3D-CT scan of a patient with trauma. Here disarticulated mandibular 3D-CT scan shows the presence of right parasymphysis and L ramus region fracture and bony fragment displacement. Shows 3D-CT scan of the same patient, but here both maxilla and mandible are seen with skull disarticulation.
This book accompanied by two DVD-ROM bearing the same call number and available at Makmal Digital Perpustakaan Dr. Abdul Latiff
Keywords: Mouth -- Surgery; Oral Surgical Procedures; Medical Sciences